O direito à celeridade processual à luz dos direitos fundamentais - Peters, Adriana Salgado (2007)
The Federal Constitution of 1988 is a landmark, as a document to protect the principle of human dignity, a cornerstone of the existence and protection of human rights. In this context, this dissertation brings to the fore a discussion on the new paradigms directed toward securing the basic right to a speedy trial. The delay of the agencies of the Public Administration and the Judicial Power in providing effective protection to the parts, in good time, is a serious problem to be solved currently, especially by reason of: the accumulation of processes, the effect of the globalization without the proportional investment in the computerization of the Public Power, the dwindling of resources destined to the Judicial Power, more efficient laws, amongst other factors. To characterize such problem, a parallel has been drawn regarding the conception of the speedy trial as a basic right of the human being, prior and subsequent to the Constitutional Amendment n.º 45, of 12-31-2004, that introduced clause LXXVIII to the Article 5º of the Federal Constitution of 1988, which assured a reasonable duration of proceedings as a basic constitutional norm and a right of the human being. Based on the analysis of this comparative picture, illustrated with up-to-date, innovative jurisprudence regarding the implementation of speedy trial, whose results are timely to the parts involved and, therefore, observant of the principles of Justice, change has been noticed in the paradigms in the Brazilian society and reconstruction of the ways to grant effective guarantee to the human rights. Therefore, it has been observed that it is time to change, time to make the process more swift for the benefit of the human being itself and for the common good of society, of which the former is a member, thus meeting the principle of the dignity of the human being in all sectors